Carbon fiber negative electrode material, preparation method thereof and lithium ion battery

By forming a carbon fiber negative electrode material with a layered porous network structure in a low eutectic solvent, the high energy consumption and insufficient performance of the existing carbon fiber preparation methods are solved, and the efficient and environmentally friendly lithium-ion battery performance is achieved promote.

CN114883528BActive Publication Date: 2024-12-13YADEA TECH GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210686008.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2024-12-13
Estimated Expiration
2042-06-16

AI Technical Summary

Technical Problem

The existing carbon fiber preparation methods have problems of high energy consumption, environmental pollution and insufficient performance. In particular, electrospinning technology limits the promotion and application of carbon fibers, and the capacity of nanocarbon fibers is not much different from graphite under low current density.

Method used

The carbon fiber negative electrode material with a layered porous network structure is used to carbonize fiber biomass carbon, halogenated choline and halogenated lithium salt in a low-melt solvent to form a carbon fiber negative electrode material. The corrosion pore formation and lithium doping during the carbonization process are used to improve the material specific surface area and lithium storage properties.

Benefits of technology

It has achieved high reversible capacity, low energy consumption and environmentally friendly carbon fiber negative electrode materials, which has improved the first Coulomb efficiency and circulation performance of lithium-ion batteries, and reduced dependence on petrochemical raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883528B_ABST
    Figure CN114883528B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon fiber negative electrode material, a preparation method thereof and a lithium ion battery. The carbon fiber negative electrode material has a porous network structure, and the carbon fiber negative electrode material includes carbon fiber and lithium carbon microspheres located at the ends of the carbon fiber. The carbon fiber negative electrode material of the present invention has a porous network structure, which is conducive to improving the specific surface area and lithium storage performance of the material, and can allow lithium ions to shuttle quickly, thereby improving its conductivity and rate performance. At the same time, the lithium carbon microspheres in the negative electrode material play a role in replenishing lithium during the charge and discharge process, promote the formation of a solid electrolyte interface film (SEI film), and greatly improve the first coulomb efficiency and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new energy technology, and relates to a carbon fiber negative electrode material, a preparation method thereof, and a lithium ion battery. Background Art

[0002] At this stage, the development of lithium-ion batteries in the new energy sector is crucial. In the research of lithium-ion batteries, the development of new high-performance electrode materials is the focus of research, among which negative electrode materials play a decisive role in improving the performance of lithium batteries. At present, the theoretical capacity of commercial graphite negative electrode materials is 372mAh / g (but about 340mAh / g in actual use), which can no longer meet people's demand for high-capacity lithium-ion batteries. Therefore, new negative electrode materials, such as nano-negative electrode materials such as carbon fiber, have attracted much attention.

[0003] The main industrial method for producing carbon fiber at present is electrostatic spinning technology, of which polyacrylonitrile (PAN)-based carbon fiber accounts for more than 90% of the total carbon fiber production, asphalt-based accounts for about 7%, and viscose filament-based accounts for about 1%.

[0004] CN113224292A discloses a high-performance lithium-ion battery polyacrylonitrile carbon fiber negative electrode material and a preparation method thereof. The preparation method comprises: dissolving polyacrylonitrile in DMF solvent, stirring fully to obtain a spinning solution; spinning the spinning solution to obtain relatively stable nanofiber filaments, and continuously spinning to obtain polyacrylonitrile precursor filaments; placing the polyacrylonitrile precursor filaments in a porcelain boat, heating in a tubular furnace under an oxygen atmosphere for pre-oxidation, cooling to room temperature to obtain pre-oxidized filaments; carbonizing the pre-oxidized filaments in a tubular furnace under a nitrogen atmosphere, and then allowing them to cool naturally to room temperature to obtain polyacrylonitrile carbon fibers; fully grinding the polyacrylonitrile carbon fibers after carbonization in an agate mortar, and drying to obtain extremely fine electrostatically spun polyacrylonitrile carbon fiber materials.

[0005] CN102560744A discloses a method for preparing general-grade asphalt-based carbon fiber, comprising: a) heating an isotropic spinnable asphalt with a softening point of 220-280°C to 270-325°C, and forming asphalt fibers through a spinning device in the chemical fiber industry; b) pre-oxidizing the asphalt fibers, with an initial temperature of 140-200°C, a final temperature of 290-350°C, and an oxidizing gas flow rate of 15-50m 3 / minute, the time is 0.9-2.8 hours, and the asphalt oxidized silk is obtained; c) the asphalt oxidized silk is carbonized, the initial temperature is 400-700°C, the final temperature is 900-1500°C, and the nitrogen flow rate is 0.5-4m 3 / minute, the carbonization time is 12-45 minutes, and general-grade asphalt-based carbon fiber is obtained.

[0006] However, the high voltage and high energy consumption of electrospinning equipment limit the promotion and application of carbon fiber. Moreover, the maximum reversible capacity of nanocarbon fiber materials obtained by electrospinning is not much different from that of graphite at a lower current density. Even if the current density is increased, the advantages of nanocarbon fiber are not so obvious.

[0007] Therefore, it is of great research significance to provide a modified carbon fiber material that is easy to prepare, green and environmentally friendly, and has higher reversible capacity. Summary of the invention

[0008] The purpose of the present invention is to provide a carbon fiber negative electrode material, a preparation method thereof and a lithium ion battery.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a carbon fiber negative electrode material, wherein the carbon fiber negative electrode material comprises carbon fibers and lithium carbon microspheres, wherein the carbon fibers are overlapped with each other to form a layered porous network structure, and the lithium carbon microspheres are located at the ends of the carbon fibers.

[0011] In the present invention, the layered porous network structure refers to: carbon fibers are overlapped to form a layered structure, and carbon fibers of different lengths are overlapped during the overlapping process to form a spatial network structure.

[0012] The carbon fiber negative electrode material of the present invention has a porous network structure, which is conducive to improving the specific surface area and lithium storage performance of the material, and can allow lithium ions to shuttle quickly, thereby improving its conductivity and rate performance. At the same time, the lithium-carbon microspheres in the negative electrode material play a role in replenishing lithium during the charge and discharge process, promoting the formation of a solid electrolyte interface film (SEI film), and greatly improving the first coulomb efficiency and cycle performance of the battery.

[0013] Compared with commercial graphite negative electrode materials, the carbon fiber negative electrode material of the present invention is very conducive to the diffusion of electrolyte and the deintercalation of lithium ions because there are many nanostructure gaps formed by the interlacing of carbon fibers between the carbon fibers. Moreover, since the carbon fiber is composed of a microcrystalline structure through van der Waals forces, the microcrystalline structure is layered, thereby forming Li2 molecules between layers, that is, forming a covalent state (position), which acts as a lithium storage warehouse. That is, in addition to storing lithium between carbon and carbon, the prepared carbon fiber material can also store lithium ions in the cavity by forming lithium molecules between layers.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the length of the carbon fiber is 2-5 μm, for example, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 3 μm, 3.3 μm, 3.6 μm, 4 μm, 4.2 μm, 4.5 μm, 4.7 μm or 5 μm, etc.; the cross-sectional diameter of the carbon fiber is 100-250 nm, for example, 100 nm, 120 nm, 130 nm, 150 nm, 188 nm, 200 nm, 210 nm, 230 nm, 240 nm or 250 nm, etc.

[0016] Preferably, the diameter of the lithium carbon microspheres is 300-500 nm, for example, 300 nm, 320 nm, 330 nm, 350 nm, 370 nm, 400 nm, 430 nm, 460 nm or 500 nm.

[0017] Preferably, the carbon fiber surface is etched to form micropores, and a porous structure is formed on the carbon fiber surface. Since the micropores are etched on the carbon fiber surface, the diameter of the micropores is very small (less than 2nm), which plays a confining role in positioning and limiting the growth of lithium carbon during lithium doping, thereby increasing the lithium storage capacity in the carbon layer and the surface of the carbon layer.

[0018] In a second aspect, the present invention provides a method for preparing the carbon fiber negative electrode material as described in the first aspect, the method comprising the following steps:

[0019] (1) heating and mixing a choline halide and a lithium halide to form a deep eutectic solvent;

[0020] (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor;

[0021] (3) Carbonizing the precursor to obtain the carbon fiber negative electrode material.

[0022] Different from the conventional carbon fiber preparation method which uses petrochemical raw materials and grain raw materials as carbon sources, the present invention uses fiber biomass carbon, a non-grain biomass, as the carbon source. The reaction process is environmentally friendly, controllable, and highly industrialized. In addition, the carbon fiber negative electrode material obtained by the method of the present invention has excellent performance.

[0023] In the method of the present invention, choline halide and halogenated lithium salt are first heated and mixed to form a low eutectic solvent. The cellulose in the fibrous biomass carbon is insoluble in water, but can swell in the low eutectic solvent to form a homogeneous mixture, which can play a role in separating cellulose. During the carbonization process, the flue gas carbonized by choline halide is alkaline, thereby producing a corrosion pore-forming effect, improving the specific surface area and lithium storage performance of the biomass carbon negative electrode material, and at the same time, the lithium salt dopes the negative electrode material to obtain lithium carbon microspheres, which play a role in replenishing lithium during the battery charging and discharging process, promote the formation of a solid electrolyte interface film (SEI), and greatly improve the first coulomb efficiency and cycle performance.

[0024] In the method of the present invention, since the fiber biomass carbon is directly carbonized with the low eutectic solvent, the phenomenon of uneven mixing of reactants in the precursor during the general carbonization process is avoided, thereby improving the carbonization efficiency and uniformity, and is suitable for industrial production.

[0025] The method of the present invention does not require the use of high-energy-consuming electrospinning technology, has the advantages of simplicity, low energy consumption, safety and environmental protection, and reduces dependence on petrochemical raw materials.

[0026] As a preferred technical solution of the method of the present invention, the choline halide in step (1) includes at least one of choline chloride, choline bromide or their derivatives.

[0027] Preferably, the halogenated lithium salt in step (1) comprises at least one of lithium chloride, lithium bromide or their derivatives.

[0028] Preferably, in step (1), the molar ratio of the choline halide to the lithium halide is (1-3):(2-8), wherein the choline halide is in the range of 1-3, for example, 1, 1.2, 1.5, 1.8, 2, 2.4, 2.8 or 3, and the lithium halide is in the range of 2-8, for example, 2, 2.5, 2.7, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7 or 8, etc.

[0029] Preferably, the temperature of the heating and mixing in step (1) is 40-80°C, for example 40°C, 43°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.; the time is 2-8h, for example 2h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 8h, etc.

[0030] Preferably, the heating and mixing process in step (1) is accompanied by stirring.

[0031] As another preferred technical solution of the method of the present invention, the fiber biomass carbon in step (2) is non-food biomass, preferably at least one of bamboo fiber, wood cellulose or its derivatives;

[0032] Preferably, in step (2), the mass ratio of the fibrous biomass carbon to the low eutectic solvent is (1-3):(2-8), wherein the selection range of the fibrous biomass carbon 1-3 can be, for example, 1, 1.5, 1.8, 2, 2.5 or 3, and the selection range of the low eutectic solvent 2-8 can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, etc.

[0033] Preferably, the mixing temperature in step (2) is 40-80°C, for example 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.; the mixing time is 2-8h, for example 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 8h, etc.

[0034] Preferably, the mixing process in step (2) is accompanied by stirring.

[0035] Preferably, after the mixing in step (2), ultrasonic oscillation and standing are sequentially performed.

[0036] Preferably, the ultrasonic oscillation is performed at room temperature.

[0037] Preferably, the ultrasonic oscillation time is 20-60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.

[0038] Preferably, the standing time is 1-2 h, for example, 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h or 2 h.

[0039] As another preferred technical solution of the method of the present invention, before the carbonization in step (3), the precursor is pre-oxidized.

[0040] Preferably, the pre-oxidation treatment temperature is 200-300°C, such as 200°C, 220°C, 240°C, 260°C, 280°C or 300°C, etc.; the holding time is 1-2h, such as 1h, 1.2h, 1.3h, 1.5h, 1.7h or 2h, etc.

[0041] Preferably, the heating rate of the pre-oxidation treatment is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0042] Preferably, the atmosphere of the pre-oxidation treatment is an oxygen-containing atmosphere, preferably an air atmosphere.

[0043] Through pretreatment, the organic matter in the mixture can be slowly decomposed and evaporated to form pores, which is conducive to obtaining high-performance carbon fiber negative electrode materials.

[0044] Preferably, the carbonization temperature in step (3) is 800-1200°C, for example 800°C, 830°C, 850°C, 900°C, 950°C, 1000°C, 1100°C, 1150°C or 1200°C, etc.; the insulation time is 6-16h, for example 6h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h, etc.

[0045] Preferably, the heating rate of the carbonization in step (3) is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0046] Preferably, the carbonization atmosphere in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes at least one of nitrogen, helium and argon.

[0047] Preferably, the carbonization in step (3) is followed by washing, separation, ball milling and sieving. The present invention does not specifically limit the separation method, for example, it may be standing, filtering, etc. The washing and separation performed in sequence is regarded as a cycle, and the number of cycles may be one or more.

[0048] Preferably, the solvent used for the cleaning is anhydrous ethanol.

[0049] Preferably, the ball mill has a rotation speed of 500-1000 r / min, such as 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, etc.; and a ball mill has a milling time of 4-6 h, such as 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc.

[0050] Preferably, the mesh number of the sieving is 180-400 mesh, such as 180 mesh, 200 mesh, 300 mesh or 400 mesh, and the sieve is taken after sieving.

[0051] In a third aspect, the present invention provides a lithium-ion battery, wherein the negative electrode material in the negative electrode of the lithium-ion battery adopts the carbon fiber negative electrode material described in the first aspect.

[0052] The present invention does not specifically limit the type of lithium-ion battery, which can be a liquid battery or a solid-state battery. For a liquid battery, it generally includes a positive electrode, a negative electrode, a separator and an electrolyte, and for a solid-state battery, it generally includes a positive electrode, a negative electrode and a solid electrolyte layer.

[0053] In some embodiments, the lithium-ion battery is a flexible battery. Since the carbon fiber negative electrode material prepared by the present invention has a porous network structure, the negative electrode has both mechanical strength and high electrochemical performance, and there are a large number of nano-voids therein, so that the flexible battery has a thinner size and a higher capacity.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] (1) The carbon fiber negative electrode material of the present invention has a porous network structure, which is conducive to improving the specific surface area and lithium storage performance of the material, and allows lithium ions to shuttle quickly, thereby improving its conductivity and rate performance. At the same time, the lithium-carbon microspheres in the negative electrode material play a role in replenishing lithium during the charge and discharge process, promoting the formation of a solid electrolyte interface film (SEI film), and greatly improving the first coulomb efficiency and cycle performance of the battery.

[0056] (2) In the method of the present invention, since the fiber biomass carbon is directly carbonized with the low eutectic solvent, the phenomenon of uneven mixing of reactants in the precursor during the usual carbonization process is avoided, thereby improving the carbonization efficiency and uniformity, and being suitable for industrial production. At the same time, the method of the present invention does not require the use of high-energy electrospinning technology, has the advantages of simplicity, low energy consumption, safety and environmental protection, and reduces dependence on petrochemical raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 and Figure 2 1 is a SEM image of the carbon fiber negative electrode material prepared in Example 1 of the present invention at different magnifications;

[0058] Figure 3 This is a SEM image of the carbon fiber negative electrode material prepared in Example 2 of the present invention;

[0059] Figure 4 This is a SEM image of the carbon fiber negative electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0061] Example 1

[0062] This embodiment provides a carbon fiber negative electrode material and a preparation method thereof, the method comprising the following steps:

[0063] 1) 13.96 g of choline chloride (C108896, Aladdin) and 21.20 g of lithium chloride (L116327, Aladdin) were weighed in a molar ratio of 1:5, and stirred at 70° C. for 2 h in a constant temperature magnetic stirrer to obtain a deep eutectic solvent;

[0064] 2) 17.28 g of lignocellulose (lignocellulose M-2, Chenqi Chemical) and 17.28 g of a deep eutectic solvent were weighed in a mass ratio of 1:1, and stirred at 60° C. for 3 h in a constant temperature magnetic stirrer to obtain a mixture;

[0065] 3) The mixture obtained in step 2) was subjected to ultrasonic oscillation at room temperature for 40 minutes using an ultrasonic machine, and then allowed to stand for 1.5 hours to obtain a precursor;

[0066] 4) The precursor obtained in step 3) is first heated to 200° C. at a heating rate of 2° C. / min in an air atmosphere and kept at this temperature for 2 h; then heated to 900° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and kept at this temperature for 12 h to obtain a reactant;

[0067] 5) The reactant obtained in step 4) was washed with anhydrous ethanol for several times and then filtered; then ball milled in a ball mill at 800 r / min for 6 h, and screened with a 270-mesh screen to obtain a carbon fiber negative electrode material, the SEM image of which is shown in Figure 1 and Figure 2 As can be seen from the figure, the carbon fiber is short chain, with a length of 2-5μm and a cross-sectional diameter of 100-250nm, and lithium carbon microspheres are generated by reaction at both ends of the carbon fiber.

[0068] This embodiment also provides a negative electrode sheet, which is prepared by the following method:

[0069] The negative electrode material obtained in this embodiment is mixed as an active material with a binder, polyvinylidene fluoride (PVDF), and a conductive agent, acetylene black, in a mass ratio of 80:15:5, and then N-methylpyrrolidone (NMP) is added and stirred evenly to form a slurry, which is then coated on the surface of a copper foil and dried in a drying oven at 80° C. for 12 h to obtain a prefabricated electrode sheet. The prefabricated electrode sheet is cut into electrode sheets after roller pressing, and dried in a drying oven at 120° C. for 8 h to obtain a negative electrode sheet.

[0070] Example 2

[0071] Different from Example 1, in step 2, 69.12 g of lignocellulose and 34.56 g of a low eutectic solvent were weighed at a mass ratio of 2:1.

[0072] The SEM image of the carbon fiber negative electrode material prepared in this Example 2 is shown in Figure 3 .

[0073] Example 3

[0074] Different from Example 1, in step 4, the precursor obtained in step 3) is first heated to 200°C at a heating rate of 2°C / min in an air atmosphere and kept warm for 2 hours; then, in a nitrogen atmosphere, the temperature is increased to 1200°C at a heating rate of 5°C / min and kept warm for 12 hours to obtain the reactant.

[0075] The difference between this embodiment and embodiment 1 is that the high temperature sintering temperature is adjusted from 900°C to 1200°C.

[0076] The SEM image of the carbon fiber negative electrode material prepared in this Example 3 is shown in Figure 4 .

[0077] Example 4

[0078] Different from Example 1, in step 2, 3.84 g of lignocellulose and 34.56 g of a low eutectic solvent were weighed at a mass ratio of 1:9.

[0079] Example 5

[0080] The difference from Example 1 is that in step 1, choline chloride and lithium chloride are weighed in a molar ratio of 1:9.

[0081] Example 6

[0082] The difference from Example 1 is that in step 1, choline chloride and lithium chloride are weighed in a molar ratio of 2:1.

[0083] Example 7

[0084] Different from Example 1, in step 4, the precursor is directly heated to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 12 hours to obtain the reactant; that is, this example does not carry out the step of heating the temperature to 200°C at a heating rate of 2°C / min under an air atmosphere and keeping warm for 2 hours.

[0085] Example 8

[0086] Different from Example 1, step 3 is not performed, and the mixture of step 2 is directly used in step 4 for pre-oxidation and high-temperature sintering, that is, the mixture of step 2 replaces the precursor of step 4.

[0087] Example 9

[0088] This embodiment provides a carbon fiber negative electrode material and a preparation method thereof, the method comprising the following steps:

[0089] 1) 13.96 g of choline chloride and 12.72 g of lithium chloride were weighed in a molar ratio of 1:3, and stirred at 60° C. for 3 h in a constant temperature magnetic stirrer to obtain a deep eutectic solvent;

[0090] 2) weighing 8.64 g of lignocellulose and 17.28 g of a deep eutectic solvent in a mass ratio of 1:2, stirring the mixture in a constant temperature magnetic stirrer at 50° C. for 6 h to obtain a mixture;

[0091] 3) The mixture obtained in step 2) was subjected to ultrasonic oscillation at room temperature for 30 minutes using an ultrasonic machine, and then allowed to stand for 1 hour to obtain a precursor;

[0092] 4) The precursor obtained in step 3) was first heated to 260° C. at a heating rate of 3° C. / min in an air atmosphere and kept warm for 1.5 h; then heated to 800° C. at a heating rate of 4° C. / min in a nitrogen atmosphere and kept warm for 14 h to obtain a reactant;

[0093] 5) The reactant obtained in step 4) was washed with anhydrous ethanol for multiple times and then filtered; then, the reactant was ball milled in a ball mill at 650 r / min for 6 h, and screened with a 270-mesh screen to obtain a carbon fiber negative electrode material.

[0094] Comparative Example 1

[0095] Different from Example 1, in step 1, 13.96 g of choline chloride and 150.00 g of urea were weighed in a molar ratio of 1:5, and stirred at 70° C. for 2 h in a constant temperature magnetic stirrer to obtain a low eutectic solvent.

[0096] Comparative Example 2

[0097] Different from Example 1, graphite is used as the active material.

[0098] Performance Test:

[0099] Preparation of half-cell: The negative electrode sheet prepared above was assembled into a lithium-ion half-cell, with lithium metal as the counter electrode, the electrolyte was a diethyl carbonate (DEC) + ethylene carbonate (EC) solution containing 1 mol / l lithium hexafluorophosphate (volume ratio DEC:EC=7:3), and the separator was polypropylene Celgard2300. After assembly in a glove box, it was allowed to stand for formation.

[0100] First discharge capacity test: The assembled battery was left to stand at room temperature for 12 hours and then subjected to constant current charge and discharge test. The charge and discharge voltage was 0-3V. The constant current charge test was performed at 25°C with a current density of 100mA / g (the charge and discharge currents were consistent). The first discharge capacity and first efficiency of the obtained lithium battery were measured.

[0101] Rate performance test: The assembled battery was left to stand at room temperature for 12 hours and then subjected to constant current charge and discharge test. The charge and discharge voltage was 0-3V. The constant current charge test was performed at a current density of 800mA / g at 25°C (the charge and discharge currents were consistent). The 8C rate performance of the obtained lithium battery was measured.

[0102] Cycle performance test: The assembled battery was left to stand at room temperature for 12 hours and then subjected to constant current charge and discharge test. The charge and discharge voltage was 0-3V. The constant current charge test was performed at a current density of 100mA / g at 25°C (the charge and discharge currents were consistent). The cycle test was terminated after 100 cycles, and the capacity retention rate of the obtained lithium battery was measured.

[0103] The performance test results of the half-cell are shown in Table 1.

[0104] Table 1

[0105]

[0106] As can be seen from Table 1, the present invention adopts halogenated choline and halogenated lithium salt to heat and mix to form a low eutectic solvent, and then carbonizes the fibrous biomass carbon after swelling treatment, so as to obtain a carbon fiber negative electrode material with a layered porous network structure modified with lithium. The carbon fiber negative electrode material has high capacity, high initial efficiency, and good rate performance and cycle performance.

[0107] Comparing Example 1 with Examples 2 and 4, it can be seen that the gram capacity and the first coulomb efficiency of Example 1 are greater than those of Examples 2 and 4. This is because the ratios of lignocellulose and low eutectic solvent in the mixture are different, and the etching effects produced when the choline cations in the low eutectic solvent decompose during sintering are different. In Example 2, the ratio of choline cations is relatively small, resulting in a small number of micropores in the negative electrode material produced by sintering, which reduces the lithium storage performance; in Example 4, the ratio of choline cations is relatively large, and although the number of micropores is increased, the solubility of lignocellulose is increased, resulting in a higher degree of granulation of the final product, an increase in specific surface area, and an increase in lithium consumption during the formation process, thereby reducing the first efficiency.

[0108] By comparing Example 1 with Example 3, it can be seen that the gram capacity of Example 1 is greater than that of Example 3. This is because as the carbonization temperature increases, more non-carbon heteroatoms are released, carbon elements are enriched, a hexagonal carbon network plane is generated, and even a turbostratic graphite structure is formed, which reduces the gram capacity.

[0109] By comparing Example 1 with Examples 5 and 6, it can be seen that the lithium specific gravity of the negative electrode material in Example 5 is higher, thereby reducing the carbon specific gravity, resulting in a decrease in gram capacity; in Example 6, the lithium specific gravity is lower, the lithium replenishment performance is lower than that in Example 1, and the initial effect is reduced.

[0110] By comparing Example 1 with Example 7, it can be seen that the electrical properties of Example 7 are generally lower. This is because the air pre-oxidation process can introduce carbonyl groups that are beneficial to electrochemical energy storage and enhance the cross-linking degree of the material; at the same time, the reactants can be further dried and easily oxidized impurities can be removed during the pre-oxidation process.

[0111] Comparing Example 1 with Example 8, it can be seen that Example 8 did not undergo ultrasonic treatment before high-temperature sintering. The ultrasonic treatment is mainly to remove dissolved gas and fine bubbles. Under ultrasonic vibration, fine bubbles collide and fuse to become larger and then float out to further disperse the reaction precursors. Therefore, ultrasound is beneficial to improving electrochemical performance.

[0112] By comparing Example 1 with Comparative Example 1, it can be seen that the first effect of Example 1 is greater than that of Comparative Example 1. This is because no lithium supplementation treatment was performed in Comparative Example 1, and the formation of SEI during formation consumed lithium, reducing the reversible capacity and the first effect.

[0113] By comparing Example 1 with Comparative Example 2, it can be seen that the gram capacity of Example 1 is greater than that of Comparative Example 2. This is because there are many pores in Example 1. In addition to storing lithium between layers, lithium is also stored on the surface of the carbon material, thereby increasing the gram capacity.

[0114] In addition, the present invention also provides a lithium ion battery, which uses the negative electrode sheet prepared in Examples 1-9. The preparation method of the lithium ion battery is as follows:

[0115] Preparation of NCM (622) positive electrode sheet:

[0116] The positive electrode active material NCM (622), the binder PVDF, and the conductive agent conductive carbon black are mixed evenly in the solvent NMP according to the mass ratio of 97:1.5:1.5. The positive electrode slurry is coated on the aluminum foil, and the NCM (622) positive electrode sheet is obtained by drying and cold pressing.

[0117] A 1 mol / l lithium hexafluorophosphate solution of diethyl carbonate (DEC) + ethylene carbonate (EC) (volume ratio DEC:EC=7:3) was used as the electrolyte, and polypropylene Celgard2300 was used as the diaphragm. After assembly in a glove box, the product was formed by standing still. The lithium-ion battery has excellent first coulomb efficiency and cycle performance. The negative electrode prepared in Example 1 was used for full battery testing: the first coulomb efficiency was 99.62%, and the 100-cycle capacity retention rate was 91.16%.

[0118] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A carbon fiber negative electrode material, characterized in that: The carbon fiber negative electrode material comprises carbon fibers and lithium carbon microspheres, the carbon fibers are overlapped with each other to form a layered porous network structure, and the lithium carbon microspheres are located at the ends of the carbon fibers; The carbon fiber surface is etched to form micropores; the diameter of the micropores is less than 2nm; The length of the carbon fiber is 2-5 μm, and the cross-sectional diameter of the carbon fiber is 100-250 nm; The carbon fiber negative electrode material is prepared by the following method, which comprises the following steps: (1) heating and mixing a choline halide and a lithium halide to form a deep eutectic solvent; (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor; and sequentially performing ultrasonic oscillation and standing steps after the mixing; (3) Carbonizing the precursor to obtain the carbon fiber negative electrode material.

2. The carbon fiber negative electrode material according to claim 1, characterized in that: The diameter of the lithium carbon microspheres is 300-500nm.

3. A method for preparing a carbon fiber negative electrode material as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: (1) heating and mixing a choline halide and a lithium halide to form a deep eutectic solvent; (2) mixing the fibrous biomass carbon with the low eutectic solvent to obtain a precursor; and sequentially performing ultrasonic oscillation and standing steps after the mixing; (3) Carbonizing the precursor to obtain the carbon fiber negative electrode material.

4. The method according to claim 3, characterized in that The choline halide in step (1) comprises at least one of choline chloride, choline bromide or their derivatives.

5. The method according to claim 3, characterized in that: The halogenated lithium salt in step (1) includes at least one of lithium chloride, lithium bromide or their derivatives.

6. The method according to claim 3, characterized in that In step (1), the molar ratio of the halogenated choline to the halogenated lithium salt is (1-3):(2-8).

7. The method according to claim 3, characterized in that The temperature of the heating and mixing in step (1) is 40-80° C. and the time is 2-8 hours.

8. The method according to claim 3, characterized in that The heating and mixing process in step (1) is accompanied by stirring.

9. The method according to claim 3, characterized in that: The fibrous biomass carbon in step (2) is non-food biomass.

10. The method according to claim 9, characterized in that The non-food biomass is at least one of bamboo fiber, wood cellulose or their derivatives.

11. The method according to claim 3, characterized in that In step (2), the mass ratio of the fibrous biomass carbon to the low eutectic solvent is (1-3):(2-8).

12. The method according to claim 3, characterized in that The mixing temperature in step (2) is 40-80° C. and the mixing time is 2-8 hours.

13. The method according to claim 3, characterized in that The mixing process in step (2) is accompanied by stirring.

14. The method according to claim 3, characterized in that The ultrasonic oscillation was performed at room temperature.

15. The method according to claim 3, characterized in that The ultrasonic oscillation time is 20-60 minutes.

16. The method according to claim 3, characterized in that The standing time is 1-2h.

17. The method according to claim 3, characterized in that Before the carbonization in step (3), the precursor is pre-oxidized.

18. The method according to claim 17, characterized in that The temperature of the pre-oxidation treatment is 200-300° C., and the insulation time is 1-2 hours.

19. The method according to claim 17, characterized in that The heating rate of the pre-oxidation treatment is 2-5°C / min.

20. The method according to claim 17, characterized in that The atmosphere of the pre-oxidation treatment is an oxygen-containing atmosphere.

21. The method according to claim 20, characterized in that The oxygen-containing atmosphere is an air atmosphere.

22. The method according to claim 3, characterized in that The carbonization temperature in step (3) is 800-1200° C. and the insulation time is 6-16 hours.

23. The method according to claim 3, characterized in that The heating rate of the carbonization in step (3) is 2-5°C / min.

24. The method according to claim 3, characterized in that The carbonization atmosphere in step (3) is an inert atmosphere, and the gas in the inert atmosphere includes at least one of nitrogen, helium and argon.

25. The method according to claim 3, characterized in that After the carbonization in step (3), the steps of washing, separation, ball milling and screening are performed in sequence.

26. The method according to claim 25, characterized in that The solvent used for the cleaning is anhydrous ethanol.

27. The method according to claim 25, characterized in that The ball mill has a rotation speed of 500-1000 r / min and a milling time of 4-6 h.

28. The method according to claim 25, characterized in that The mesh number of the sieving is 180-400 meshes, and the sieve under is taken after sieving.

29. A lithium ion battery, characterized in that: The negative electrode material in the negative electrode of the lithium ion battery adopts the carbon fiber negative electrode material according to claim 1 or 2.

30. The lithium ion battery according to claim 29, characterized in that The lithium ion battery is a flexible battery.

Citation Information

Patent Citations

  • Method for preparing universal pitch-based carbon fiber

    CN102560744A

  • High-performance lithium ion battery polyacrylonitrile carbon fiber negative electrode material and preparation method thereof

    CN113224292A

  • Carbon-nitrogen-lithium multi-phase doped lithium ion battery negative electrode material, preparation method of material, lithium ion battery negative electrode plate and lithium ion battery

    CN109888181A